Design of experiments approach for modeling the electrical response of a photovoltaic module - Fatma Zohra Kessaissia; Abdallah Zegaoui; Rachid Taleb; Chahinez Fares; Michel Aillerie (Institute of Advanced Engineering and Science, 2020)
In the current paper, modeling and evaluation of the significant effect of independent variables on the behavior of the electrical response of a multi-crystalline photovoltaic (PV) module using design of experiments (DoE) approach is simulated. The main purpose of this contribution is to evaluate the maximum power response dependence within the indoor conditions of both variations of solar irradiation and surface temperature and checking the pertinent one on the defined response. the DoE approach is used for estimating both main and combined effect of the two independents considered variables. Multiple linear regression was been introduced to justify the relationship between the independent input variables and dependent output variable, also to determine which input factor is the most significant on the output variable. The DoE model can be used for predicting the response variable at different operating condition in a considered domain study. In addition, DoE approach based on statistical tool for analyzing the accuracy of the predictive model, then the significance of coefficients in the predictive model using statistical and graphical analysis. Therefore, an ANOVA Table can summarize the results, detect the parameters influences on responses variations and determine the best predictive model then reproduce the most possible the experimental data.